THE INFLUENCE OF SCIENTIFIC APPROACH TO FIQIH LEARNING ON STUDENT LEARNING OUTCOMES - Firdausy, Naufal Salim; Shobirin, Mochammad Syafiuddin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
The aims of this study were to find out whether there was an effect of the scientific approach on fiqh learning on students' cognitive, affective, and psychomotor learning outcomes at MA Al-Bairuny Sambong Dukuh. This study uses a quantitative research approach with the type of experimental research. The population in this study were all students of class XI MA Al-Bairuny Sambong Dukuh which consisted of two classes. The sampling technique in this study used saturated sampling used 2 classes, namely class XI IPS 1 as the control class and class XI IPS 2 as the experimental class. The data collection method in this study used the test, questionnaire, documentation, and observation methods, while the data analysis technique in this study used the T-test. The results showed, (1) There was an effect of the scientific approach on fiqh learning on cognitive learning outcomes as indicated by Sig level value. 0.000 < 0.05, (2) There is an effect of the scientific approach on learning fiqh on affective learning outcomes indicated by the value of the Sig level. 0.000 < 0.05, and (3) There is an effect of the scientific approach on learning fiqh on psychomotor learning outcomes as indicated by the value of the Sig level. 0.000 < 0.05. This research will become a reference for measuring the effectiveness of the scientific approach presented by educational practitioners on various student abilities.